Twisted Roots - Andrews, Virginia (London Simon & Schuster, 2004)
Following "Willow" and "Wicked Forest", this is the third novel in the spine-tingling De Beers series
Keywords: Rich people -- Teenage girls -- Florida--Palm Beach